The Baudelaire fractal - Robertson, Lisa, 1961- (Toronto : Coach House Books, 2020)
"A debut novel by acclaimed poet Lisa Robertson, in which a poet realizes she has written the works of Baudelaire. One morning, the poet Hazel Brown wakes up in a strange hotel room to find that she's written the complete works of Charles Baudelaire. Surprising as this may be, it's no more surprising to Brown than the impossible journey she's taken to become the writer that she is. Animated by the spirit of the poète maudit, she shuttles between London, Vancouver, Paris, and the French countryside, moving fluidly between the early 1980s and the present, from rented room to rented room, all the while considering such Baudelairian obsessions as modernity, poverty, and the perfect jacket. Part memoir, part magical realism, part hilarious trash-talking take on contemporary art and the poet's life, The Baudelaire Fractal is the long-awaited debut novel by the inimitable Lisa Robertson."--
boek
Keywords: Baudelaire, Charles, -- 1821-1867.